Live-cell RNA imaging using the CRISPR-dCas13 system with modified sgRNAs appended with fluorescent RNA aptamers. Issue 47 (14th November 2022) - Tang, Heng; Peng, Junran; Peng, Shuang; Wang, Qi; Jiang, Xin; Xue, Xiaocheng; Tao, Yanxin; Xiang, Limin; Ji, Quanjiang; Liu, Song-Mei; Weng, Xiaocheng; Zhou, Xiang
Abstract : The development of RNA imaging strategies in live cells is essential to improve our understanding of their role in various cellular functions. Abstract : The development of RNA imaging strategies in live cells is essential to improve our understanding of their role in various cellular functions. We report an efficient RNA imaging method based on the CRISPR-dPspCas13b system with fluorescent RNA aptamers in sgRNA (CasFAS) in live cells. Using modified sgRNA attached to fluorescent RNA aptamers that showed reduced background fluorescence, this approach provides a simple, sensitive way to image and track endogenous RNA with high accuracy and efficiency. In addition, color switching can be easily achieved by changing the fluorogenic dye analogues in living cells through user-friendly washing and restaining operations. CasFAS is compatible with orthogonal fluorescent aptamers, such as Broccoli and Pepper, enabling multiple colors RNA labeling or intracellular RNA–RNA interaction imaging. Finally, the visualization of severe fever with thrombocytopenia syndrome virus (SFTSV) was achieved by CasFAS, which may facilitate further studies on this virus.